2016
DOI: 10.1021/acscatal.6b01771
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methanol to Olefins over H-ZSM-5 Zeolite: Reaction Pathway Is Related to the Framework Aluminum Siting

Abstract: As the conversion of methanol to olefins (MTO) over a zeolite catalyst is conducted on acid sites derived from framework aluminum (AlF), it is possible to enhance the catalytic performance by altering the siting of AlF if one knows the catalytic behavior of specified AlF located at certain sites. In this work, two series of H-ZSM-5 zeolites, viz., S-HZ-m and T-HZ-m, were synthesized with silica sol and tetraethyl orthosilicate, respectively, as the silicon source. Both series of H-ZSM-5 zeolites exhibit simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(237 citation statements)
references
References 91 publications
13
206
0
2
Order By: Relevance
“…Although high Brønsted site densities result in faster deactivation due to faster coking rates, not only Brønsted acid site density but also distribution play an important role. Wang et al 7 showed that the same concentration of Brønsted acid sites can still lead to different lifetime due to an uneven Al distribution and formation of Al pairs. Analysis of Al distribution assessed by UV-Vis of Co-exchanged zeolites shows that this distribution within α-, β-and γ-sites is rather similar (Supplementary Figure 12), excluding the effect of Al location.…”
mentioning
confidence: 99%
“…Although high Brønsted site densities result in faster deactivation due to faster coking rates, not only Brønsted acid site density but also distribution play an important role. Wang et al 7 showed that the same concentration of Brønsted acid sites can still lead to different lifetime due to an uneven Al distribution and formation of Al pairs. Analysis of Al distribution assessed by UV-Vis of Co-exchanged zeolites shows that this distribution within α-, β-and γ-sites is rather similar (Supplementary Figure 12), excluding the effect of Al location.…”
mentioning
confidence: 99%
“…The fact that these two structures outperform other structures with similar pore sizes and acid strength for a lot of reactions, like FCC, MTH and alkane/alkene conversion was also assigned to confinement effects. They influence in which configuration reactants interact with the active site and are believed to play a significant role in determining the activity of those two zeolite topologies . Kosinov et al .…”
Section: Topology Brønsted Acidity and The Aromatization Reactionsmentioning
confidence: 99%
“…The two materials showed similar intrinsic acidity, morphology and textural properties. Yet, the conversion of methanol by T‐HZ gives higher selectivity to ethylene and aromatics than by S‐HZ, which, in turn, provides higher selectivity to propene and higher olefins . Similarly, the crucial role of the pore size and shape for the methanol to olefin (MTO) conversion was revealed by DFT calculations .…”
Section: Brønsted Acidity Of Zeolitesmentioning
confidence: 99%